Human embryonic stem cells secrete soluble factors that inhibit cancer cell growth - Giuffrida, D. (Cell Prolif, 2009)
Objectives:  The aim of this study was to determine whether normal human embryonic stem cells (hESC) would secrete factors that arrest growth of human epithelial cancer cell lines. Materials and methods:  Cell proliferation was examined using the MTT assay then haemocytometer cell counts. Staining with propidium iodide followed by flow cytometry was used to detect cell cycle stages. Heat denaturation and molecular fractionation experiments were also performed. Results:  We found that hESC conditioned medium (hESC CM) inhibited SKOV‐3 and HEY cell proliferation. Similar results were also obtained when we used breast and prostate cancer cell lines, whereas little or no inhibitory effect was observed when human fibroblasts were tested. Moreover, a co‐culture model confirmed that inhibition of cancer cell proliferation is mediated by soluble factors produced by hESCs. We also determined that the proportion of cancer cells in G(1) phase was increased by hESC CM treatment, accompanied by decrease in cells in S and G(2)/M phases, suggesting that the factors slow progression of cancer cells by cell cycle inhibition. Heat denaturation and molecular fractionation experiments indicated a low molecular weight thermostable factor was responsible for these properties. Conclusions:  Our findings provide evidence that the human embryonic microenvironment contains soluble factor(s) that are capable of inhibiting growth of cancer cells, and that exposure to such factors may represent a new cancer treatment strategy.